Probiotics—role in alleviating the impact of alcohol liver disease and alcohol deaddiction: a systematic review - Vidya Bernhardt, Grisilda; Shivappa, Pooja; R. Pinto, Janita; KS, Rashmi; Ramakrishna Pillai, Jayachithra; Kumar Srinivasamurthy, Suresh; Paul Samuel, Vijay (Frontiers in Nutrition, 2024)
Background: There are few efficient treatment options for alcohol addiction, which continues to be a serious public health concern. The possible contribution of gut microbiota to the onset and progression of alcohol addiction has been brought to light by recent studies. Probiotics have become a cutting-edge intervention in the treatment of alcohol consumption disorder because of its favorable effects on gut health. The purpose of this systematic review is to assess the body of research on the advantages of probiotics in treating alcoholism and associated neuroinflammatory conditions. Methods: To find pertinent research published from January 2012 to 2023, a thorough search of electronic databases, including PubMed, Scopus, Google Scholar and Web of Science, was carried out. Included were studies looking at how probiotics affect neuroinflammation, gut- brain axis regulation, alcohol addiction, and related behaviors. Findings: Several investigations have shown how beneficial probiotics are in reducing systemic inflammation and alcoholic liver disease (ALD). Probiotic treatments successfully corrected the imbalance of microbiota, decreased intestinal permeability, and stopped the passage of bacterial constituents such lipopolysaccharides (LPS) into the bloodstream. Additionally, probiotics helped to regulate neurotransmitter pathways, especially those connected to GABA, glutamate, and dopamine, which are intimately linked to behaviors related to addiction. Furthermore, it was shown that probiotics altered the expression of neurotransmitter signaling and dopamine receptors. Conclusions: There is strong evidence from this systematic study that probiotics have potential advantages in treating alcohol addiction. The potential of probiotic therapies is demonstrated by the way they modulate important neurotransmitter pathways implicated in addiction, decrease neuroinflammation, and restore the balance of gut flora. To fully investigate the therapeutic potential of probiotics in treating alcohol addiction and enhancing the general wellbeing of those afflicted by this condition, more research is necessary.